THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND THEIR SPEAKING ACHIEVEMENT AT SENIOR HIGH SCHOOL 4 KENDARI - Anggraini, Desy; Kamaluddin, Kamaluddin; Siam, Siam (Journal of Teaching of English, 2020)
The  objective  of  this  study  was  to  determine  the  correlation between  the   students‟  motivation  and   their   speaking  competence at grade 11 of Senior High School 4 Kendari. The design of this study was quantitative research and the population was all grade 11 students at Senior High School 4 Kendari with the total numbers of students was 620  students.  The  sample  of  this  study  was  class  XI  MIA  7  (36 students). The instrument of this study were questionnaire and students‟  speaking  score. The researcher collected the data by using questionnaire adapted from Sun (2009) as the data of students‟ motivation  and  final  speaking  score  to  get   data   about   students‟ speaking achievement. To analyze the data, the researcher used descriptive  statistic  to   view  the   students‟ speaking  achievement and their motivation based on five categories are; very low, low, medium, high, and very high. The   result of  this   study  showed  that  students‟ speaking achievement was mostly categorized in good criteria. It also showed that the students were highly motivated to learn speaking English by using video blog. The result of inferential statistics analysis showed that there was  a significant  correlation between students‟ motivation and their speaking achievement at grade 11 of Senior High School 4 Kendari. It was proved by the result of product moment correlation (rxy = 0.487), which was higher than r-table = 0.329.It means that motivation and achievement had a positive correlation.